The third secret : a novel - Berry, Steve (New York : Ballantine Books, 2006)
When Pope Clement XV becomes obsessed with the Virgin Mary's revelations at Fatima in 1917, his papal secretary begins to fear the Pope's obsession may uncover a shocking truth about the Church that has been hidden for many years.
Keywords: Catholics -- Fiction; Suspense fiction